Cytotaxonomy of four Floral Variants of Impatiens Balsamina L. (Journal of Bangladesh Academy of Sciences, 2019)
Karyomorphological characters were investigated in four floral variants of Impatiens balsamina L. viz. white, pink, violet and red for proper characterization and inferring relationships among them. All four floral variants of I. balsamina were found to possess 2n = 14 chromosomes, and ‘Simple Chromocenter Type’ of interphase nuclei was observed in all variants with many small heterochromatin blocks after orcein staining. ‘Continuous Type’ of prophase chromosomes was found in red variant, whereas both ‘Continuous and Gradient Type’ were found in other three variants. The red variant could easily be distinguished from the remaining three variants by total chromosome length, centromeric formula, average chromosome length, total form value, and karyotype asymmetry plus symmetry index. Based on karyomorphology, the white, pink and violet variants of I. balsamina were found very closely related and constituted with similar genome, whereas red variant was found to possess slightly modified genome and distinct from other three floral variants.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 1-9, 2019